2008
DOI: 10.1165/rcmb.2007-0139oc
|View full text |Cite
|
Sign up to set email alerts
|

MARCKS Regulation of Mucin Secretion by Airway Epithelium in Vitro

Abstract: We have reported previously that myristoylated alanine-rich C kinase substrate (MARCKS) is a key regulatory molecule controlling mucin secretion by airway epithelial cells in vitro and in vivo. The results of those studies supported a mechanism whereby MARCKS, upon phosphorylation by protein kinase C (PKC), translocates from plasma membrane to cytoplasm, where its binding to membranes of intracellular mucin granules is a key component of the secretory pathway. It remains unknown how MARCKS is targeted to and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…F-actin crosslinking activity of MARCKS is also reduced following phosphorylation (Arbuzova et al, 2002). Phosphorylated MARCKS translocates either to the cytosol or nucleus, where it has been shown to co-localize with a diverse array of cellular complexes, including components of the secretory pathway as well as γ-tubulin (Park et al, 2008). Surprisingly, we found that phosphorylation by PKC is not crucial for the role of MARCKS in radial glial cell polarization.…”
Section: Functional Domains Of Marcks and Their Relevance In Radial Gmentioning
confidence: 58%
See 1 more Smart Citation
“…F-actin crosslinking activity of MARCKS is also reduced following phosphorylation (Arbuzova et al, 2002). Phosphorylated MARCKS translocates either to the cytosol or nucleus, where it has been shown to co-localize with a diverse array of cellular complexes, including components of the secretory pathway as well as γ-tubulin (Park et al, 2008). Surprisingly, we found that phosphorylation by PKC is not crucial for the role of MARCKS in radial glial cell polarization.…”
Section: Functional Domains Of Marcks and Their Relevance In Radial Gmentioning
confidence: 58%
“…When unphosphorylated, the PSD domain binds calmodulin with high affinity, crosslinks F-actin and binds to multivalent lipids, including PIP 2 and PS (Blackshear et al, 1992;Hartwig et al, 1992;Sundaram et al, 2004). Phosphorylation of the PSD domain decreases the electrostatic interaction of MARCKS with the plasma membrane, thus facilitating release of MARCKS from the membrane (Park et al, 2008;Swierczynski and Blackshear, 1995;. F-actin crosslinking activity of MARCKS is also reduced following phosphorylation (Arbuzova et al, 2002).…”
Section: Functional Domains Of Marcks and Their Relevance In Radial Gmentioning
confidence: 99%
“…We propose that phosphorylation of MARCKS, triggered as an early event of the LPS stimulation, leads to its dissociation from the cell membrane and translocation to the endosomes, where it can bind to LPS and downregulate the excessive activation of TLR4. MARCKS translocation to endosomes may also involve additional chaperones, similarly as translocation to mucin granules mediated by cysteine string protein (63). Efficiency of the myristoylation-deficient A2/G2 mutant of MARCKS, which under the normal conditions resides in the cytoplasm and associates with endosomes upon LPS stimulation, further supports this mechanism.…”
Section: Discussionmentioning
confidence: 77%
“…MARCKS regulates the hypersecretion of mucus in respiratory diseases, such as asthma and cystic fibrosis (70,81). Phosphorylation of MARCKS allows movement to the cytoplasm, binding to chaperone HSP70, which engages the cysteine string protein located on the surface of the secretory vesicles containing mucin (69,82). Because apoE is structurally a mucin, we hypothesize a similar model for apoE secretion, and future research will delineate the exact chaperone molecules and mechanisms through which MARCKS regulates both basal and stimulated apoE secretion.…”
Section: Discussionmentioning
confidence: 88%